Indeks Kepuasan Masyarakat Kelompok Penerima Manfaat Program CSR PT Pembangkit Listrik Jawa Bali (PJB) UP Muara Karang - Rindang Matoati; Eko Ruddy Cahyadi (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2019)
The success of PembangkitListrikJawa Bali (PJB) UP MuaraKarang ‘s Corporate Social Responsibility (CSR) Program is inseparable from the solid collaboration between the community and the CSR’s staff of PT PJB’s UP MuaraKarang. PT PJB MuaraKarang is a unit of PT PJB which achieved a green propeer in 2016. To keepits achievements, it is important to do a continuous study of the extent of the level of community satisfaction carried out so that program performance continues improvement. The data collection was obtained by distributing questionnaires to 30 community respondents who were community members. The communities that were used as the object of research were the mangrove community, folding houses and also the Trash Bank community living in the MuaraAngke area, North Jakarta. Based on the results of the analysis using IPA and CSI show that overall the level of satisfaction of the community or community members towards the implementation of the Social Responsibility program of PT PJB UP MuaraKarang brought good results (86.17%.)